A theoretical review on the interplay of EFL/ESL teachers' career adaptability, self-esteem, and social support - Xue, Yuxiu (Frontiers in Psychology, 2022)
Second/foreign language education has been considered a complex profession due to the interaction of numerous internal and external factors. Owing to such complications, the teaching profession is seen as a tough task for which L2 teachers must be psychologically ready. In order to provide an effective education, teachers need to have career adaptability to manage the challenges and transition of roles in academia. This ability may be affected by many factors like teachers’ self-esteem and perceived social support. Despite the significance of these three constructs, few (if any) studies have focused on their interaction. Against this lacuna, this study presented a theoretical review of the concepts, definitions, dimensions, and related studies to EFL/ESL teachers’ CA, self-esteem, and social support. The study also offers some implications for teachers, trainers, school principals, and researchers trying to increase their awareness of psycho-social factors involved in L2 education.